Homocysteine Induced Dementia: Collecting Evideneces for Alzheimer’s Disease - Vivek Kumar Sharma (International Journal of Pharma and Bio Sciences, 2010)
Alzheimer disease and vascular dementia are two most common types of dementia. Initially treated as etiologically different disorders, the two subtypes of dementia have been shown to share several pathological features. Over the last two decades, research has focused on identifying potentially modifiable risk factors in development and progression of dementia and has identified dietary related factors such as the B-vitamin group including folate, vitamin B12, vitamin B6 and related metabolites such as homocysteine as important in cognitive functioning. Homocysteine is a sulfur amino acid and a normal intermediate in methionine metabolism. When excess homocysteine is produced in the body and not readily converted into methionine or cysteine, it is excreted out of the tightly regulated cell environment into the blood. It is the role of the liver and kidney to remove excess homocysteine from the blood. The risk of atherothrombotic events of the heart, brain and limbs is increased due to high blood HCys. Current review is an effort to update and sum up the evidences for Homocysteine to regard it as a definite pathological factor for Alzheimer’s disease.